2008
DOI: 10.1080/10409280802230973
|View full text |Cite
|
Sign up to set email alerts
|

Quality in Inclusive Preschool Classrooms

Abstract: Research Findings: Quality of care for preschool children in inclusive and noninclusive classrooms was examined in two studies. In Study 1, comparisons across a large sample of classrooms (N = 1, 313) showed that inclusive classrooms were higher than noninclusive classrooms in global quality as well as on two dimensions of quality (Activities/Materials and Language/Interactions). In Study 2, a more diverse sample of 44 classrooms (20 inclusive and 24 noninclusive) did not reveal differences on the global measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
3
25
0
6
Order By: Relevance
“…However, contact with children with disabilities may not be the only difference in the experience of children within inclusive and noninclusive classes. For example, research has revealed that children from inclusive preschool classrooms, compared to children from noninclusive classrooms, experienced qualitatively higher levels of interactions with teachers (Hestenes, Cassidy, Shim, & Hegde, ). Thus, inclusive settings may be more likely to provide an emotionally supportive environment, which represents an important condition for children's social adjustment (Murray & Pianta, ).…”
Section: Social Exclusion About Disability In Switzerlandmentioning
confidence: 99%
“…However, contact with children with disabilities may not be the only difference in the experience of children within inclusive and noninclusive classes. For example, research has revealed that children from inclusive preschool classrooms, compared to children from noninclusive classrooms, experienced qualitatively higher levels of interactions with teachers (Hestenes, Cassidy, Shim, & Hegde, ). Thus, inclusive settings may be more likely to provide an emotionally supportive environment, which represents an important condition for children's social adjustment (Murray & Pianta, ).…”
Section: Social Exclusion About Disability In Switzerlandmentioning
confidence: 99%
“…Additionally, teachers with two years of college achieved significantly higher scores than those with high school diplomas and some college. Recent analyses on this large dataset show a moderate association between teacher education and global quality (r = .29; Hestenes, Cassidy, Shim, & Hegde, 2008).…”
Section: Teacher Educationmentioning
confidence: 89%
“…Limited research is specifically available on instructional quality for children with disabilities; some research shows that ECSE classrooms exhibit low instructional quality (Buysse, Wesley, Bryant, & Gardner, 1999; Guo, Sawyer, Justice, & Kaderavek, 2013; Pelatti, Dynia, Logan, Justice, & Kaderavek, 2016; cf. Hestenes, Cassidy, Shim, & Hegde, 2008; Spear et al, 2018). Nonoptimal instruction may partially explain results from the Pre-Elementary Longitudinal Study, indicating minimal improvement in the language and literacy skills of preschool children with disabilities (Carlson et al, 2008).…”
Section: Need For Ecse Language and Literacy Interventionsmentioning
confidence: 99%